Non-Productive Infection of Glial Cells with SARS-CoV-2 in Hamster Organotypic Cerebellar Slice Cultures - Lise Lamoureux; Babu Sajesh; Jessy A. Slota; Sarah J. Medina; Matthew Mayor; Kathy L. Frost; Bryce Warner; Kathy Manguiat; Heidi Wood; Darwyn Kobasa; Stephanie A. Booth (Viruses, 2022)
The numerous neurological syndromes associated with COVID-19 implicate an effect of viral pathogenesis on neuronal function, yet reports of direct SARS-CoV-2 infection in the brain are conflicting. We used a well-established organotypic brain slice culture to determine the permissivity of hamster brain tissues to SARS-CoV-2 infection. We found levels of live virus waned after inoculation and observed no evidence of cell-to-cell spread, indicating that SARS-CoV-2 infection was non-productive. Nonetheless, we identified a small number of infected cells with glial phenotypes; however, no evidence of viral infection or replication was observed in neurons. Our data corroborate several clinical studies that have assessed patients with COVID-19 and their association with neurological involvement.